Covidom, a Telesurveillance Solution for Home Monitoring Patients With COVID-19 - Yordanov, Youri; Dechartres, Agnes; Lescure, Xavier; Apra, Caroline; Villie, Pascaline; Marchand-Arvier, Jerome; Debuc, Erwan; Dinh, Aurélien; Jourdain, Patrick (JMIR Publications, 2020)
In a matter of months, COVID-19 has escalated from a cluster of cases in Wuhan, China, to a global pandemic. As the number of patients with COVID-19 grew, solutions for the home monitoring of infected patients became critical. This viewpoint presents a telesurveillance solution-Covidom-deployed in the greater Paris area to monitor patients with COVID-19 in their homes. The system was rapidly developed and is being used on a large scale with more than 65,000 registered patients to date. The Covidom solution combines an easy-to-use and free web application for patients (through which patients fill out short questionnaires on their health status) with a regional control center that monitors and manages alerts (triggered by questionnaire responses) from patients whose health may be deteriorating. This innovative solution could alleviate the burden of health care professionals and systems while allowing for rapid response when patients trigger an alert.